Loss of Histone Deacetylase 4 in Hepatocytes Increases De Novo Lipogenesis in Diet-Induced Obesity Mice - Lee, Yoojin; Bae, Minkyung; Chamberlain, Dana; Pham, Tho; Kang, Hyunju; Kim, Mi-Bo; Hu, Siqi; Park, Young-Ki; Lee, Ji-Young (Current developments in nutrition, 2020)
Evidence suggests that histone deacetylase 4 (HDAC4) is downregulated in adipose tissue of obese subjects. We determined the role of HDAC4 in the regulation of energy metabolism of metabolically active tissues, such as the liver and adipose tissue. Hepatocyte-specific (Hdac4HKO) and adipocyte-specific (Hdac4AKO) Hdac4 knockout mice were generated by crossing homozygous Hdac4 floxed (Hdac4fl/fl) mice with mice expressing Cre recombinase under the control of the enhancer/promoter of Albumin or Adipoq gene, respectively. Hdac4fl/fl and Hdac4HKO mice were fed a high fat/high sucrose (HF/HS; 57%/28% energy from fat/sucrose) with 2% cholesterol (w/w) diet for 16 weeks. Hdac4fl/fl and Hdac4AKO mice were fed an obesogenic HF/HS diet for 16 weeks. The final serum was collected by cardiopuncture for blood analysis. Tissues were snap frozen for mRNA and protein analysis. Both Hdac4HKO and Hdac4AKO mice did not show differences in body weight compared to Hdac4fl/fl mice following the 16-week of experimental diet. However, loss of hepatic HDAC4 increased serum alanine transaminase levels, a marker for liver injury. Also, Hdac4HKO mice had exacerbated hepatic steatosis with higher liver weights and triglyceride levels than Hdac4fl/fl mice. Consistently, hepatic expression of genes for de novo lipogenesis, including Srebf1c and its target genes, fatty acid synthase and acetyl CoA carboxylase 1, was significantly higher in Hdac4HKO mice compared with control mice. Interestingly, the loss of hepatocyte HDAC4 aggravated inflammation and fibrosis in white adipose tissue. Serum cytokine array indicated increases in fibroblast growth factor 1, pentraxin 3, tissue inhibitor of metalloproteinases 1, and decrease in endocan, which may contribute to the crosstalk between the liver and adipose tissue in Hdac4HKO. On the other hand, the loss of adipocyte HDAC4 elicited minimal changes in mRNA levels of lipogenic, inflammatory, and fibrogenic genes in adipose tissue and the liver. The lack of functional hepatocyte HDAC4 increased lipid accumulation in the liver of obesity mice via increasing hepatic de novo lipogenesis, and also aggravated adipose tissue inflammation and fibrosis. Further investigation is warranted to elucidate the crosstalk between the liver and adipose tissue in Hdac4HKO. This study was supported by NIH.